Using MEST-C Scores and the International Study of Kidney Disease in Children Classification to Predict Outcomes of Henoch–Schönlein Purpura Nephritis in Children - Wang, Meiqiu; Wang, Ren; He, Xu; Zhang, Pei; Kuang, Qianhuining; Yao, Jun; Fang, Xiang; Shi, Zhuo; Wu, Heyan; Peng, Yingchao; Xia, Zhengkun; Gao, Chunlin (Frontiers in Pediatrics, 2021)
Introduction: Henoch–Schönlein purpura nephritis (HSPN) and IgA nephropathy (IgAN) bear similarities in some aspects. The histological classification of HSPN was built on the International Study of Kidney Disease in Children (ISKDC) criteria, while IgAN was established on the 2016 Oxford classification (MEST-C scores). The purpose of this paper was to discuss the predictive value of the ISKDC classification and MEST-C scores in children with HSPN. Methods: We performed a retrospective study of 877 children with HSPN in a single center between 2001 and 2019. The primary outcome was defined as chronic kidney disease—estimated glomerular filtration rate (eGFR) <90 ml/min/1.73 m2. Results: During the follow-up period of 23.3 (10.9–47.9) months, 51 (5.8%) patients reached the primary outcome. As revealed in a Kaplan–Meier plot, segmental glomerulosclerosis (S) (P < 0.001) and tubular atrophy/interstitial fibrosis (T) (P < 0.001) significantly predict poor renal outcome. Other Oxford lesions and the ISKDC classification, however, did not show a significant difference in a worse outcome. In a multivariate Cox model adjusted for pathological and clinical factors, eGFR [hazard ratio (HR) = 2.831, 95% confidence interval (95% CI) = 1.359–5.896], S lesion (HR = 3.936, 95% CI = 2.078–7.457), and T lesion (HR = 4.002, 95% CI = 1.733–9.242) were independent risk factors for the renal outcome. Conclusion: This series constitutes the largest series reported so far in the literature of such patients. According to our findings, S and T of the Oxford classification, which are ignored by the ISKDC classification, could be applied to predict the renal prognosis of children with HSPN.